Review of Irish Women and Nationalism : Soldiers, New Women and Wicked Hags, edited by Louise Ryan and Margaret Ward - Sophie van Os (Review of Irish Studies in Europe)
Review of Irish Women and Nationalism : Soldiers, New Women and Wicked Hags (New Edition), edited by Louise Ryan and Margaret Ward (Dublin: Irish Academic Press, 2019). 240pp, €24.95, paperback.